Comfort level of a cross laminated timber (CLT) structure from Sesenduk timber in Forest Research Institute Malaysia - Husain, Hamdan (MAJ - Malaysia Architectural Journal, 2020)
Thermal comfort is a key criterion to be considered to ensure a healthy indoor environment for the occupants. In Malaysia, cross laminated timber (CLT) is gaining favour in the building sector owing to the depletion resources of timbers. An 18 m2 cross laminated timber (CLT) structure were built at the Forest Research Institute Malaysia. However, there is lacking of information on the thermal comfort of CLT structure in Malaysia. Therefore, this study aimed to determine the temperature and relative humidity variation within the CLT structure over a period of one year. The environmental parameters such as temperature and relative humidity were recorded daily at every 30 minutes from 730 to 1730. The data recording was implemented for over a year from January 2018 to December 2018. Graphs were plotted using mean monthly data as well as the hourly data on the specific day. The results revealed that the CLT structure provide a sound insulation against heat as when the temperature outside is scorching hot, the occupants can still find comfort in the house. Nevertheless, there is still some rooms of improvement for the CLT structure to be implemented in the future study, especially the ventilation rate.